Faktor Penghambat Minat Berwirausaha dikalangan Mahasiswa (Studi Survei) - Dede Mustomi; Khoirul Ulum; Aprilia Puspasari; Ayu Azizah (Jurnal Administrasi Bisnis, 2021)
Entrepreneurship is a forum for college students or alumni to work and practice the knowledge learned in college. However, in practice, many students have not yet entered into entrepreneurship. Why this happens, the writer tries to find the answer by surveying student respondents to find out their obstacles when talking about entrepreneurship. The purpose of this study is to determine the points that become obstacles for students to start entrepreneurship. This research is a descriptive study using a survey method and using a purposive sampling technique, where the authors randomly distribute questionnaires to respondents from among active students totaling 120 people. The survey period was conducted for one month in the period April 2021. Of the 120 questionnaires distributed, all of them were returned and filled in by respondents. The result was that the survey statement regarding capital was chosen by the majority of respondents as many as 49 respondents as the variable that most inhibited students' interest in starting entrepreneurship and the lowest variable was the variable prohibited by parents which was only chosen by 5 student respondents.